The hellfire club - Tapper, Jake (Little, Brown and Company, 2018)
After a mysterious fatal car accident kills his predecessor, Congressman Charlie Marder struggles to navigate the dangerous waters of 1950s Washington, D.C., where he finds an underworld of backroom deals, secret societies, and a conspiracy at the highest levels of the government.